The Impulse Buying of Gen-Z in Surabaya When Using Digital Payment with Gender as Moderation - Kasuma, Putri Ayu; Immanuel, Dewi Mustikasari; Dewi, Yuli Kartika (Universitas Brawijaya, Indonesia, 2024)
Gen Z is a potential buyer both now and in the future, characterized by their familiarity with technology, including digital payment methods. Therefore, it is crucial to understand the connection between this generation and impulse buying, as the ease of using digital payments can significantly influence their purchasing behavior. This research examines Gen Z's impulse-buying tendencies at Universitas Ciputra Surabaya when using GOPAY. A quantitative approach is employed, utilizing Partial Least Squares Structural Equation Modeling (PLS-SEM) to analyze relationships between variables. A sample of 396 GOPAY users was selected using purposive sampling techniques through an online questionnaire. The data show that the model accounts for 22.5% of the variance in Perceived Enjoyment and 36.6% in Impulse Buying. Perceived Interactivity and Visual Appeal are two important factors of Perceived Enjoyment, with Visual Appeal ranking as the most influential. Furthermore, the study uses gender as a moderating variable, demonstrating that female users are more receptive to interactive elements, which increases their Perceived Enjoyment and impulsive purchasing inclinations. Gender did not, however, modify the effects of Visual Appeal on Perceived Enjoyment or the link between Perceived Enjoyment and Impulse Buying. This study contributes to the existing literature by providing insights into gender-specific responses to e-wallet design elements. Practical implications suggest that GOPAY developers should consider gender-tailored strategies to increase user engagement and impulsive purchases among Gen Z.